Effect of combined training with balance, strength, and plyometrics on physical performance in male sprint athletes with intellectual disabilities - Jouira, G.; Rebai, H.; Alexe, D. I.; Sahli, S. (Adapted Physical Activity Quarterly, 2024)
Individuals with intellectual disabilities often face unique challenges in physical capabilities, making traditional training methods less effective for their specific needs. This study aimed to investigate the effect of combining balance, plyometric, and strength (CBPS) training with sprint training on physical performance in male athletes with intellectual disabilities. Twenty-seven participants were randomly assigned to either a CBPS group or a control group that only maintained their regular sprint training. Participants underwent pre- and posttraining tests, including measures of balance, jumping, agility, and sprinting ability. The results showed that the CBPS group demonstrated significant improvements (p < .05) in one-leg stance, crossover-hop jump, squat jump, countermovement jump, and 10- and 30-m sprint at posttraining compared with pretraining. CBPS training combined with sprinting significantly improves physical performance in male athletes with intellectual disabilities, suggesting implications for tailored training programs to enhance their physical fitness and overall health.